PEMANFAATAN CAMPURAN BATANG JAGUNG DAN BAMBU SEMBILANG SEBAGAI BAHAN BAKU PAPAN PARTIKEL - Dede Hermawan1; Jajang Sutiawan; Nofrisman Jaya Putra Zendrato; Robi’atul Utami Aini; Ismail Budiman; Kurnia Wiji Prasetyo (BRIN Publishing, 2020)
Corn stalk (Zea mays L.) can be used as an alternative material in the manufacture of particleboards. However,particleboards made from corn stalks has inferior mechanical properties which could not meet the Japanese standard(JIS A 5908: 2003). Such performance can be improved by adding other material which possesses high strength value,such as bamboo sembilang (Dendrocalamus giganteus Munro). This study examined properties of cornstalkparticleboard which was added into bamboo sembilang fibers in various compositions. Urea formaldehyde and phenolformaldehyde were used as binding agent with 10% adhesive content. Composition of fiber mixtures between corn stalkand sembilang bamboo were set in 100 : 0; 75 : 25; 50 : 50; and 25 : 75. The targetted density of particleboardwas set at 0.80 g/cm3. Mechanical properties of the produced particleboards were evaluated according to JIS A5908:2003 standard. Results showed that particleboard produced using composition of 25% corn stalk and 75%sembilang bamboo bonded with phenol formaldehyde had better mechanical properties than those of the other mixtureraw materials and adhesives. Additional high strength of lignocellulose material such as bamboo is one alternative toenhance mechanical properties of cornstalk particleboard.